2018
DOI: 10.3892/etm.2018.6714
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients with late spontaneous recanalization of the atherosclerotic occlusion of internal carotid arteries: A pilot case series

Abstract: Late spontaneous recanalization (SR) of an occluded internal carotid artery (ICA) has been rarely reported and the prognosis of affected patients remains elusive. In the present study, the incidence of late SR of atherosclerotic occlusion of the ICA and associated outcomes were assessed in a single center. A total of 36 patients with ICA occlusion, who underwent carotid artery stenting or vertebral artery stenting in arteries other than the occluded ICA, were prospectively included and followed up for ≥18 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…She had new symptoms 1 month later and was successfully treated with recanalization by stenting and angioplasty. At the 9-month follow-up, she did not have any neurological symptoms [52]. Stenting and angioplasty may be a therapeutic option in select patients with chronic total carotid occlusion.…”
Section: Recanalization At 1-3 Months After Onsetmentioning
confidence: 92%
See 1 more Smart Citation
“…She had new symptoms 1 month later and was successfully treated with recanalization by stenting and angioplasty. At the 9-month follow-up, she did not have any neurological symptoms [52]. Stenting and angioplasty may be a therapeutic option in select patients with chronic total carotid occlusion.…”
Section: Recanalization At 1-3 Months After Onsetmentioning
confidence: 92%
“…Patients with late SR of the ICA tended to have preserved neurological function and favorable clinical outcomes. Large-scale studies are needed, as this study was too small to perform reliable statistical analysis [52]. Shojima et al reported that 7 out of 8 patients with ICA occlusion for an average time of 19.4 ± 7.3 months were successfully recanalized, resulting in improved ipsilateral cerebral hemodynamics without symptomatic stroke.…”
Section: Recanalization At 3 Months or Later After Onsetmentioning
confidence: 93%
“…Patients with late SR of the ICA appear to have preserved functional ability and favorable clinical outcomes. 18 months follow-up mRS score was 2 ( Wu et al, 2018 ). In a case of study by Terada et al (2005) , a 73 old male with ICA occlusion presenting after 79 days post clinical symptoms appeared.…”
Section: Clinical Evidence On Delayed Revascularizationmentioning
confidence: 97%
“…Rare cases of late spontaneous revascularization of internal carotid artery (ICA) have been reported. Wu et al (2018) reported the late spontaneous revascularization (SR) of ICA occlusion in 36 patients. The follow-up of the patients was done for more than 18 months.…”
Section: Clinical Evidence On Delayed Revascularizationmentioning
confidence: 99%